Information practices in multi-professional work in urban planning - Anna Suorsa; Anna-Maija Multas; Emilia Rönkkö; Eevi Juuti; Anelma Lammi; Heidi Enwald (Information Research: An International Electronic Journal)
Introduction. This study investigates information practices to develop multi-professional work in the planning of healthy living environments in and around urban planning.